A novel oscillation control for MEMS vibratory gyroscopes using a modified electromechanical amplitude modulation technique. (19th December 2016) - Ma, Wei; Lin, Yiyu; Liu, Siqi; Zheng, Xudong; Jin, Zhonghe
Abstract: This paper reports a novel oscillation control algorithm for MEMS vibratory gyroscopes using a modified electromechanical amplitude modulation (MEAM) technique, which enhances the robustness against the frequency variation of the driving mode, compared to the conventional EAM (CEAM) scheme. In this approach, the carrier voltage exerted on the proof mass is frequency-modulated by the drive resonant frequency. Accordingly, the pick-up signal from the interface circuit involves a constant-frequency component that contains the amplitude and phase information of the vibration displacement. In other words, this informational detection signal is independent of the mechanical resonant frequency, which varies due to different batches, imprecise micro-fabrication and changing environmental temperature. In this paper, the automatic gain control loop together with the phase-locked loop are simultaneously analyzed using the averaging method and Routh–Hurwitz criterion, deriving the stability condition and the parameter optimization rules of the transient response. Then, a simulation model based on the real system is set up to evaluate the control algorithm. Further, the proposed MEAM method is tested using a field-programmable-gate-array based digital platform on a capacitive vibratory gyroscope. By optimizing the control parameters, the transient response of the drive amplitude reveals a settling time of 45.2 ms without overshoot, according well with the theoretical prediction and simulation results. The first measurement results show that the amplitude variance of the drive displacement is 12 ppm in an hour while the phase standard deviation is as low as 0.0004°. The mode-split gyroscope operating under atmospheric pressure demonstrates an outstanding performance. By virtue of the proposed MEAM method, the bias instability and angle random walk are measured to be 0.9° h −1 (improved by 2.4 times compared to the CEAM method) and 0.068° (√h) −1 (improved by 1.4 times), respectively.